Rajabhat University Education Policy and Image of Suan Sunandha Rajabhat University’s Thai dance and theatre - et. al., Manissa Vasinarom, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article aims to study the relations between Rajabhat university education policy and the image of Thai Classical Dances Program of Suan Sunandha Rajabhat University. The scope of the study focuses on the policy of Suan Sunandha Rajabhat University, located in Bangkok, between 2004 – 2021, by studying from document, interview, observation, and small group discussion. The results showed that, the prominent policy of Suan Sunandha Rajabhat University is to be the smart archetypal university of the society in education, research, academic service, and preservation of art and culture. With the mission to become the university for community, this emphasizes the image of the Faculty of Fine and Applied Arts, Department of Performing Arts (Thai Classical Dances). The faculty has various personnel with outstanding identity, who are academic practitioners, proficient in communication, skillful in thinking, and full of public mind. The contribution to the public can be divided into 4 categories; teaching and practice service, performing arts documentary research, field study, and experimental service; academic service with innovative teaching methods; performance arrangement service, academic seminar, research, and activities for the community; preservation service for art and culture, conservation, succession, and development according to the royal initiative of King Rama X. With the variation in image and organization culture that support for self-development of the personnel and organization as a whole, the Thai Classical Dances Program of Suan Sunandha is well known in both national and international level..